2019
DOI: 10.3389/fpls.2019.00468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waterlogging-Induced Autophagy on Programmed Cell Death in Arabidopsis Roots

Abstract: Autophagy, a highly conserved process in eukaryotes that involves vacuolar degradation of intracellular components and decomposition of damaged or toxic constituents, is induced by endogenous reactive oxygen species (ROS) accumulation, endoplasmic reticulum stress, and other factors. In plants, the role of autophagy in the induction of programmed cell death (PCD) is still unclear. Here, we show that ROS contribute to the regulation of PCD during waterlogging (which results in oxygen depletion) via autophagy. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 71 publications
(95 reference statements)
0
25
0
Order By: Relevance
“…Lysigenous aerenchyma contributes to the ability of plants to tolerate low-oxygen soil environments by providing an internal aeration system for the transfer of oxygen from the shoot. However, aerenchyma formation requires Programmed Cell Death (PCD) in the root cortex (Drew et al, 2000;Bartoli et al, 2015;Fujimoto et al, 2018;Guan et al, 2019). Interestingly, both the aerenchyma formation and PCD in waterlogged sunflower stems are promoted by ethylene and ROS (Steffens et al, 2011;Petrov et al, 2015;Ni et al, 2019).…”
Section: Ros Functions In Aerenchyma Formationmentioning
confidence: 99%
“…Lysigenous aerenchyma contributes to the ability of plants to tolerate low-oxygen soil environments by providing an internal aeration system for the transfer of oxygen from the shoot. However, aerenchyma formation requires Programmed Cell Death (PCD) in the root cortex (Drew et al, 2000;Bartoli et al, 2015;Fujimoto et al, 2018;Guan et al, 2019). Interestingly, both the aerenchyma formation and PCD in waterlogged sunflower stems are promoted by ethylene and ROS (Steffens et al, 2011;Petrov et al, 2015;Ni et al, 2019).…”
Section: Ros Functions In Aerenchyma Formationmentioning
confidence: 99%
“…Studies using different plant species and tissues have shown that AOX amount can change in response to hypoxia, anoxia, or reoxygenation after a low oxygen treatment (Amor et al, 2000;Tsuji et al, 2000;Klok et al, 2002;Szal et al, 2003;Millar et al, 2004;Liu et al, 2005;Kreuzwieser et al, 2009;Skutnik and Rychter, 2009;Narsai et al, 2011;Gupta et al, 2012;Vergara et al, 2012;Rivera-Contreras et al, 2016;Vishwakarma et al, 2018;Guan et al, 2019;Panozzo et al, 2019;Wany et al, 2019). The majority, but not all, of these studies indicate an increase of AOX transcript, protein and/or maximum activity (capacity) under such conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The first ATG gene was identified from yeast, and at least 32 ATGs have been shown to participate in yeast autophagy [5,6]. To date, many homologues of ATGs have been identified from various plant species, including 40 AtATGs in Arabidopsis [1,3] (Arabidopsis thaliana, At), 33 OsATGs in rice [7] (Oryza sativa, Os), 30 NtATGs in tobacco [8] (Nicotiana tabacum, Nt), 45 ZmATGs in maize [9] (Zea mays, Zm), 29 CaATGs in pepper [10] (Capsicum annuum, Ca), 37 SiATGs in foxtail millet [11] (Setaria italic, Si), 32 MaATGs in banana [12] (Musa acuminate, Ma), and 35 VvATGs in grapevine [13] (Vitis vinifera, Vv). According to the reported characterizations of ATGs in yeast and Arabidopsis, these ATGs can be divided into the following functional groups: (1) the ATG1/13 kinase complex consisting of ATG1, ATG13, ATG20, and TOR (target of rapamycin kinase), mainly functioning on autophagy induction and initiation; (2) the PI3K (phosphatidylinositol 3 kinase) complex consisting of ATG6, VPS15 (vacuolar protein sorting-associated protein), and VPS34 that is involved in vesicle nucleation and autophagosome formation; (3) the ATG9/2/18 complex consisting of ATG9, ATG2, and ATG18 that is responsible for the delivery of membranes for autophagosome formation; (4) the ubiquitin-like ATG8-PE (phosphatidylethanolamine) conjugation pathway (including ATG3, ATG4, ATG7, and ATG8) and ATG12-ATG5 conjugation pathway (including ATG5, ATG7, ATG10, ATG12, and ATG16) that are involved in the elongation of autophagic vesicles; and (5) the VTI12 (vesicle transport v-soluble N-ethylmaleimide-sensitive-factor attachment protein receptor (SNARE) protein) family belonging to the SNARE group, which contributes to the fusion of autophagosomes with vacuoles [1][2][3][4]6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Shinozaki et al proved that autophagy played important role in maintaining zinc bioavailability to avoid ROS accumulation under zinc deficiency in Arabidopsis [31]. Moreover, the potential roles of autophagy in waterlogging and excess aluminum and copper stresses were also reported [13,32,33].…”
Section: Introductionmentioning
confidence: 99%